Hubungan Kepemimpinan Situasional, Disiplin Kerja, dan Komitmen Organisasional Terhadap Kinerja Guru SD Gugus IV Kecamatan Buleleng - N. Santika; I.G.K.A Sunu; K.R. Dantes (Pascasarjana Universitas Pendidikan Ganesha, 2021)
The problem in this study is whether there is a relationship between situational leadership, work discipline, and organizational commitment to the performance of teachers in Elementary School Group IV, Buleleng District. The purpose of this study was to determine the magnitude of the relationship of situational leadership, work discipline, and organizational commitment to the performance of teachers in Elementary School Cluster IV Buleleng District. This study is an